Molecular design of sulfonated hyperbranched poly(arylene oxindole)s for efficient cellulose conversion to levulinic acid. Issue 6 (16th November 2015) - Yu, Feng; Thomas, Joice; Smet, Mario; Dehaen, Wim; Sels, Bert F.
Abstract : This contribution is about various sulfonated hyperbranched poly(arylene oxindole)s (SHPAOs) prepared via a convenient A2 + B3 polycondensation and subsequent sulfonation as water-soluble and recyclable acid catalysts for the conversion of cellulose to levulinic acid (LA). Abstract : This contribution is about the design and synthesis of various sulfonated hyperbranched poly(arylene oxindole)s (SHPAOs) with different substituents via a convenient A2 + B3 polycondensation and subsequent sulfonation as water-soluble and recyclable acid catalysts for the conversion of cellulose to levulinic acid (LA). Whereas their molecular weight (from 2.7 × 10 3 to 20.2 × 10 3 ), acid density (from 3.4 to 4.8 mmol H + per g) as well as the polymer structure, viz . hyperbranched or linear analogues, only slightly affect the catalytic performance, the presence of electron-withdrawing substituents on the isatin polymer building block is key to their catalytic efficiency. Among all polymer catalyst designs studied, the use of 5-Cl-SHPAO provided the highest LA yield of almost 50%, directly obtained from ball-milled cellulose in aqueous medium at 165 °C, being twice the LA yield of that of unsubstituted SHPAOs. The presence of the 5-chloro-substituent substantially facilitates the hydrolysis of the glycoside bonds. The close vicinity of the oxindole functionality to the sulfonic acid group seems essential to realize such high hydrolysis rates, as chemical protection of the NH group or sulfonation at other positions lead to substantially lower LA yields. The presence of the 5-chlorine substituent also retards the glucose isomerisation rate, while slightly increasing the HMF conversion rate to LA. As a result, the catalytic reaction progresses in conditions of low concentrations of the most reactive intermediates, fructose and HMF, that otherwise could lead to considerable humin formation. Though hydrophobic interactions are usually invoked to explain such catalytic effects, this contribution suggests also a significant role of the steric proximity of the sulfonic acid group to the oxindole NH group, enabling a kinetic optimization of the reaction cascade through molecular design of the catalytically active acid site.